Performance Evaluation of 3x1 MW Mini Hydro Power Plant in Malili District, East Luwu Regency - Irfan, Nafil Rif'at (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2025)
One form of simple renewable energy that is widely used is water energy (hydro power). one form of water energy utilization is the MiniHydro power plant,. MHP was chosen as an alternative energy because it has several advantages over other power plants, such as being environmentally friendly, more durable, smaller operating costs and suitable for remote areas. The purpose of this research is to evaluate the performance of the plant in terms of continuity of service and analyze the factors that affect the continuity of service of the plant and analyze the level of reliability of the plant based on the value of energy availability produced by the MHP. the methods in this research are literature study, observation, data collection and processing. Based on the results of the study, it is known that the electrical energy produced by the Ussu Malili MHP for one year (2023) amounted to 16,439,486 kWh and the resulting energy efficiency reached 67%. The resulting operating time is 81%, maintenance time reaches 3.9%, and disruption time is 21%, while the reliability of the power system based on the availability of energy at the Ussu Malili MHP is 79%.